The potential of intercropping food crops and energy crop to improve productivity of a degraded agriculture land in arid tropics - I K D Jaya; N Nurrachman; J Jayaputra (Journal of Degraded and Mining Lands Management, 2014)
Degraded agricultural lands in the arid tropics have low soil organic carbon (SOC) and hence low productivity. Poor farmers that their livelihoods depend highly on these types of lands are suffering. Cropping strategies that are able to improve the soil productivity are needed. In the present study, some intercropping models of food crops with bio-energy crop of castor (Ricinus communis L.) were tested to assess their potential to improve the degraded land productivity. The intercropping models were: (1) castor - hybrid maize, (2) castor – short season maize, (3) castor – mungbean, and (4) castor –short season maize – mungbean. The results show that yields of the component crops in monoculture were relatively the same as in intercropping, resulted in a high Land Equivalent Ratio (LER). The highest LER (3.07) was calculated from intercropping castor plants with short season maize crops followed by mungbean with intercropping productivity of IDR 15,097,600.00 /ha. Intercropping has a great potential to improve degraded agriculture land productivity and castor is a promising plant to improve biodiversity and area coverage on the land.